2019
DOI: 10.4103/ija.ija_548_18
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan for patients with heart failure undergoing major oncological surgery: A randomised blinded pilot study

Abstract: Background and Aims:Cardiovascular diseases and cancer are among the leading causes of mortality worldwide. The aim of this study is to evaluate the efficacy and safety of preoperative administration of levosimendan in patients with chronic heart failure (CHF) scheduled for major abdominal oncologic surgery.Methods:This study included 60 patients with abdominal malignancy, ejection fraction (EF) <35% and CHF scheduled for surgery under isoflurane-fentanyl anaesthesia and were managed in the surgical intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…In the sensitivity analysis, excluding any single trial did not significantly alter the overall combined OR (P-value ranging from <0.00001 to <0.0001). Similarly, subgroup analyses confirmed the higher successful weaning rates in patients with low LVEF and MV (27)(28)(29)31), patients with ECMO after cardiac surgery (11,17,24,30), and patients with ECMO and cardiogenic shock (9, 10, 15, 22, 25) (Figure 2). However, levosimendan showed no beneficial effect on patients with MV weaning difficulty than the control group (12,16,23,26) (Figure 2).…”
Section: Primary Outcomementioning
confidence: 63%
See 4 more Smart Citations
“…In the sensitivity analysis, excluding any single trial did not significantly alter the overall combined OR (P-value ranging from <0.00001 to <0.0001). Similarly, subgroup analyses confirmed the higher successful weaning rates in patients with low LVEF and MV (27)(28)(29)31), patients with ECMO after cardiac surgery (11,17,24,30), and patients with ECMO and cardiogenic shock (9, 10, 15, 22, 25) (Figure 2). However, levosimendan showed no beneficial effect on patients with MV weaning difficulty than the control group (12,16,23,26) (Figure 2).…”
Section: Primary Outcomementioning
confidence: 63%
“…The main characteristics of included studies and predefined outcome measures are shown in Table 1 and Additional File 3 . Fourteen observational studies ( 9 11 , 15 17 , 22 – 26 , 30 – 32 ) and four RCTs ( 12 , 27 – 29 ) were included, which were conducted between 2009 and 2021. All but two studies ( 12 , 28 ) were single-center studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations